How does corporate ESG performance affect sustainable development: A green innovation perspective - Lian, Yonghui; Li, Yaqi; Cao, Hong (Frontiers in Environmental Science, 2023)
This study examines the influence of corporate ESG performance on green innovation based on the data of 2024 A-share listed firms in China from 2009 to 2020. We find that ESG performance has a significantly positive impact on green innovation. Mechanism analysis reveals that excellent ESG performance contributes to relieving financing constraints, enhancing the level of corporate human capital, and improving management myopia, thus positively influencing corporate green innovation. Heterogeneity analyses show that the effect is more pronounced among non-state-owned enterprises, enterprises in non-polluting industries, and enterprises in market-oriented areas. Further analyses prove that good ESG performance also helps to enhance the quality of green innovation, the efficiency of green innovation, and the proportion of collaborative green innovation. These results offer important implications for improving firm ESG performance and promoting corporate green innovation.